PENGARUH MOTIVASI, KESEJAHTERAAN DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI PT. AGROTECH PESTICIDE INDUSTRY MEDAN - Indra Bakti Nasution (Universitas Islam Islam Sumatera Utara, 2020)
The Problem formulation in this research is how the influence of motivation, welfare and the spirit of WORK on the performance of the employee PT. Agrotech Pesticide Industry Medan, and the purpose of this research is To know and analyze The influence of motivation, welfare and the work spirit to the performance of employees at PT. Agrotech Pesticide Industry Medan. This research is a quantitative descriptive study. Data collection techniques are conducted through interviews,questionnairequestions and documentation studies. The samples in this study were as many as 45 employees. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The Results of the test in Unison showed that motivation, prosperity and the spirit of work positively and significantly affect the performance variables of employees PT. Agrotech Pesticide Industry Field coefficient value of determination of 0.637 or 63.7%. Partially, the motivation has a positive and significant impact on the employee's performance of PT. Agrotech Pesticide Industry Medan with a regression coefficient value of 0.432 or 43.2%. Prosperity has a positive and significant effect on the performance of employees of PT. Agrotech Pesticide Industry Medan with a regression coefficient value of 0.347 or 34.7%. The Spirit of work positively and significantly influence the employee performance of PT. Agrotech Pesticide Industry Medan with a regression coefficient value of 0.305 or 30.5%. The highest value of a regression coefficient is a motivation of 0.432 or 43.2%